2013
DOI: 10.12669/pjms.292.3151
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis: Clinical and demographic features in an African population

Abstract: Objective: To describe the clinical and demographic features of patients with visceral leishmaniasis (VL), from Sudan, Africa. Methodology: A descriptive study was conducted during 5 years period on confirmed VL patients. These patients are, originally, from White Nile Province (WNP) region, a previously non-endemic VL focus which is located in southern part of Sudan. They were referred during the period 2006-2010 for management at Tropical Diseases Hospital (TDH) in the capital Khartoum. The patients data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…This difference was found statistically significant (p<0.05). Similar findings were obtained by earlier studies conducted elsewhere [ 27 – 32 ]. However, large spleen (4–6 cm) size was also noticed for only negligible proportion under this study.…”
Section: Discussionsupporting
confidence: 93%
“…This difference was found statistically significant (p<0.05). Similar findings were obtained by earlier studies conducted elsewhere [ 27 – 32 ]. However, large spleen (4–6 cm) size was also noticed for only negligible proportion under this study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, hematologic manifestations were high compared to previous studies done in North West Ethiopia and Greece. 18,19 This is likely due to late presentation which leads to bone marrow suppression by the amastigote and inflammation and splenic sequestration from huge splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] VL affects mainly of hematopoietic system manifested with leukopenia (96.6%), anemia (94.9%), thrombocytopenia (90.5%), and pancytopenia. [17][18][19][20][21][22][23][24] VL is diagnosed using serologic tests (either direct agglutination test (DAT) or recombinant kinesin protein (RK-39) dipstick) and confirmed parasitologically by the microscopic demonstration of amastigotes of Leishmania donovani bodies in Giemsa-stained tissue aspirates of the spleen, bone marrow, or lymph node. 15 In resource-limited areas or inconclusive results, VL can be diagnosed by case definition.…”
mentioning
confidence: 99%
“…The clinical manifestations of VL observed in the present study are concordant with those reported by other studies 41 , 48 . Fever, weakness, hepatomegaly, weight loss and splenomegaly were frequent among VL cases and comprise the classic clinical features of the disease, generally found at the patients admission 49 . Curiously, anemia and pancytopenia (blood dyscrasias) were not detected at high frequencies, although pallor was often reported.…”
Section: Discussionmentioning
confidence: 99%